Effect of Medicinal Plant Byproducts on Carcass Traits, Meat Composition and Sensory Attributes in Broiler Chicken (Annals of Bangladesh Agriculture, 2025)
Several types of medicinal plants are consumed for their pharmacological properties. However, the byproducts generated after their use as herbal products are often unutilized, contributing to environmental pollution despite containing valuable nutrients and bioactive compounds. Therefore, current study was conducted to investigate the efficacy of byproducts derived from three different medicinal plants (Aloe vera, Camelia sinensis and Phylanthus emblica) on carcass traits, meat chemical composition and sensory attributes of broiler chicken. Four different types of dietary treatments include 1) MPBC0: Control (basal diet without medicinal plant byproduct combinations; 2) MPBC1 = basal diet + 0.2% medicinal plant byproduct combinations; 3) MPBC2 = basal diet + 0.4% medicinal plant byproduct combinations; 4) MPBC3 = basal diet + 0.6% medicinal plant byproduct combinations tested. The result of the present study revealed that among the dietary treatments, MPBC1, MPBC2 and MPBC3 exhibited no negative influence on carcass traits (P<0.05); however, some internal organ weight differed among dietary treatments (P<0.05). The proximate composition of broiler meat was significantly improved in broilers treated with MPBC1, MPBC2, and MPBC3 compared to those treated with MPBC0 (P<0.05). Similarly, sensory evaluation results indicated that broilers treated with MPBC1, MPBC2, and MPBC3 had better meat quality attributes as compared to MPBC0 (P<0.05). In conclusion, medicinal plant byproducts could be a potent feed additive source for better meat quality attributes with little alteration on carcass traits and internal organ weight in case of broiler chicken.Ann. Bangladesh Agric. 28(1): 79-90